Determination of The Sequence of Intersecting Lines on Writing and Signature Examination - Hamzaoğlu, Nurcan; Yavuz, Mustafa Fatih (The Bulletin of Legal Medicine, 2018)
Objective: In this study, how effectively the stereo microscopes can be used in the crossings created using both the same kind of (ballpoint pen) ink (homogeneous) and different types of (pen/inkjet-laser printer) inks (heterogeneous). Material and Methods: In order to decide the effectiveness of the stereo microscope in detecting the upside-down relation of the crossing lines and the time of the formation for these lines, homogeneous and heterogeneous crossing line samples prepared by using 3 different black ballpoint pens, 3 different blue ballpoint pens, laser printer and inkjet printer are analyzed by fourteen experienced document examination experts via their own methods and by authors using stereo microscope. Results: In the examinations conducted by fourteen document examination experts with loop; the total line detection rate in the heterogeneous samples where the laser printer and inkjet printer prints and the ink lines are crossing changes between 33% and 83%, and the average detection rate is 60%. However, in the homogeneous samples created with black and blue ballpoint pens, line detection rates were found to be significantly low in determining the order of the crossing lines. Average line detection rate is 43%. In the same samples, an examination was carried authors by using stereo microscope; while reliable results could not be obtained in the homogeneous crossings, confidential results were obtained in the heterogeneous crossings. Conclusions: Consequently, it was decided that the formation order by stereo microscope can be capably and effectively determined in the heterogeneous crossings consisting of ballpoint pen and printer print.